PELATIHAN PENGOLAHAN SELAI DAN MARMALADE BUAH NAGA, PENDAMPINGAN DIGITAL MARKETING DAN PENGELOLAAN KEUANGAN DI PEKON GEDUNG SURIAN LAMPUNG BARAT - Majidah, Rona; Noer Fathia, Syaharani; Octary, Ayu Dwiny; Eka Putri, Widya Rizki (BEGAWI : Jurnal Pengabdian Kepada Masyarakat, 2024)
Rural areas are areas with great potential for agro-industrial development. This development is related to increasing the added value of products in anticipation of falling agricultural product prices when the harvest season arrives. So far, the community has not optimized the processing of the village's superior products and only sells them as raw materials. The service team intends to provide training in processing superior village products for the community, both community groups, MSMEs, and home industries in order to increase the community's economic independence and introduce financial management. One area that has superior village products is Pekon Gedung Surian which is located in Gedung Surian District, with the majority of the population being farmers, who produce several commodities, one of which is dragon fruit. Through dragon fruit processing training, dragon fruit shelf life and added value will be increased, so that it can boost the economy of the community in Pekon Gedung Surian. Furthermore, by providing training and assistance on digital marketing and financial management, sales of these products can be increased.